Tailoring of structural and photoluminescence emissions by Mn and Cu co-doping in 2D nanostructures of ZnS for the visualization of latent fingerprints and generation of white light. Issue 4 (15th January 2019) - Kumbhakar, Partha; Biswas, Subrata; Pandey, Prafull; Tiwary, Chandra S.; Kumbhakar, Pathik
Abstract : The "one-stone-two-birds" model for the simultaneous tuning of morphology and luminescence in Mn–Cu co-doped ZnS nanosheets for the detection of latent fingerprints. Abstract : There has been a recent demand for the development of luminescent materials for visualizations of latent fingerprints (LFPs) for achieving enhanced security. Also recently, there has been a new research trend in the development of 2D materials from non-layered semiconductors with strong luminescence properties in the visible region. The conventional growth process of luminescent materials limits their capacity of tuning the structure and light emission efficiency. However, multi-atom doping provides an additional degree of freedom to tune the basic morphologies and optical properties of luminescent semiconductors by controlling the defect levels. Here, by using a simple chemical technique, multi-atom (Cu and Mn) doped rarely reported 2D nanosheets of zinc sulphide (ZnS) have been grown. Thus, a stable high fluorescence efficiency of ∼62% in the visible region has been realized for the visualization of LFPs. Furthermore, near-white light emission has been demonstrated by coating the synthesized materials with a suitable doping concentration on a commercially available UV-LED chip. The proposed technique may be utilized further to build up other 2D nanostructured materials for multifunctional applications in solid state lighting, LFPs and forensic science.